Genetic control of grain yield and its primary components in bean plants - Santos, João Bosco dos; Vencovsky, Roland; Ramalho, Magno Antonio Patto (Pesquisa Agropecuaria Brasileira, 2014)
Seven bean (Phaseolus vulgaris L.) cultivars were crossed following a half-diallel model and data were obtained from the parents and F2 generation, in order to determine the genetic control of grain yield and its primary components. A randomized block design with three replications was used in two locations of Minas Gerais State, Brazil, in 1981. The method proposed by Jinks and Hayman for analyzing diallel crosses was used, and the data met the assumptions of the model, except in three cases, where an adjustment was necessary to fit the model. The additive gene action was predominant in relation to dominance for all traits. Consequently, one should consider the mean behavior of the cultivars and of the segregant populations to carry out a breeding program. There was a significant interaction between gene action and locations.